FACTORS - FACTORS THAT INFLUENCE CHOICE OF PROFESSIONAL ACCOUNTANTS IN PUBLIC AND NON PUBLIC ACCOUNTANTS ACCOUNTING DEPARTMENT FOR STUDENTS IN YOGYAKARTA SPECIAL REGION - MS, Cynthia; H. Supardi, Drs. (Accounting, 2009)
The role of accountants educators as a stimulant in this regard is felt very important. Accounting profession educators are always working to improve the benefits of the course material being taught to their students. The same subject may be presented differently or given different emphasis. Globally high diperguruan accounting teaching tends to direct the student to work as a public accountant (Widhinugroho, 1999). Students who wish to work as an accountant and wants to take the certification exam necessary to follow the profession of education so that the socialization of professional accounting education programs should be increased. Therefore, accountants educators need to think about and consider the interests of students for the course material can be effectively delivered in accordance with the goals of students in participating in education. Businesses that require accounting graduates need to know the various factors to be considered by job seekers in receiving a job offer. This is very helpful in the process of mutually beneficial relationships between job seekers with employers. The results showed that compared with students who chose public accounting profession, students who choose non-public accounting profession in greater consideration of the intrinsic value of a job and starting salaries are high. On the other hand, students who choose to work as a public accountant is more promising. Related to the ratio of benefits to costnya, students who chose public accounting profession believes that the award of this profession is greater than sacrifice. While students who choose non-public accounting profession thought that the sacrifice to become a public accountant will be greater than the benefits gained. Keywords : accountants in public, non public accountants